The Effect Of Locus Of Control, Budget Emphasis and Budget Participation On Information Asymmetry and Its Impact On Budgetary Slack - Emalia Fitri; Wirmie Eka Putra; Yudi Yudi (International Journal of Economics and Management Research, 2024)
This research aims to determine the influence of locus of control, budget emphasis and budget participation on the budgetary slack with information asymmetry as an intervening variable in the Regional Apparatus Organization (OPD) of Kerinci Regency. The population in this study includes all Regional Regional Apparatus Organization (OPD) in Kerinci Regency, totaling 42 OPD with respondents taken namely the Head of OPD, OPD Secretary, Finance Section and Program Planning Section. The research sample was selected using saturated sampling, namely a sampling technique using the entire population as a research sample consisting of 168 respondents. This research method uses quantitative methods. This research uses primary data obtained through questionnaires distributed to respondents. The research results show that locus of control has a negative effect on the budgetary slack, while budget emphasis and budget participation have a positive effect on the budgetary slack. locus of control and budget emphasis have a positive effect on information asymmetry, while budget participation has a negative effect on information asymmetry. Information asymmetry is able to mediate the influence of locus of control, budget emphasis and budget participation on the budgetary slack.